Overwintering Honey Bee Colonies in Northern Climates - James D. Ellis; Katherine Hammons (EDIS, 2013)
One of the many challenges beekeepers face is minimizing honey bee colony losses during winter. This can be especially challenging to beekeepers in extreme northerly climates. Special preparations must be made during the fall to ensure that colonies survive the winter months with minimal loss. This 3-page fact sheet was written by James D. Ellis and Katherine Hammons and published by the UF Department of Entomology and Nematology, September 2013.